Preterm prelabour rupture of membranes: a retrospective cohort study of association with adverse outcome in subsequent pregnancy. (28th December 2016) - Aris, IM; Logan, S; Lim, C; Choolani, M; Biswas, A; Bhattacharya, S
Abstract : Objective: To assess the association of first pregnancy preterm prelabour rupture of membranes (PPROM) with adverse maternal and perinatal outcomes in the next pregnancy. Design: Retrospective cohort study. Setting: Grampian, Scotland, UK. Population: Women with first deliveries recorded in the Aberdeen Maternity Neonatal Databank, 1986–2005. Methods: Women identified from the AMND database ( n = 37 776) were classified into exposed (PPROM in first pregnancy; n = 1979) and unexposed (no PPROM in first pregnancy; n = 35 797) cohorts. Each cohort (exposed n = 1174; unexposed n = 20 860) was followed up until December 2012 for next singleton pregnancy. Main outcome measures: Second pregnancy, miscarriage, pregnancy‐induced hypertension (PIH), pre‐eclampsia (PE), antepartum haemorrhage (APH) and postpartum haemorrhage, repeat PPROM, type of labour, mode of delivery, preterm delivery, low birth weight (LBW), admission to neonatal unit, neonatal infections and death. Results: PPROM in the first singleton pregnancy was associated with an equal likelihood of second pregnancy but with a significantly increased risk of adverse outcomes in the next singleton pregnancy: PPROM [odds ratio (OR) (95% confidence interval (CI)): 6.6 (5.4–7.9)], PE [2.4 (1.7–3.5)], instrumental [2.2 (1.7–2.8)] and caesarean delivery [1.8 (1.5–2.3)], PIH [1.5 (1.2–1.9)] and APH [1.3 (1.1–1.6)] in the mother, and neonatal infection [5.4 (1.4–20.3)], death [2.6 (1.0–6.7)], admission to neonatal unit [2.4 (2.0–2.9)], preterm delivery [2.3 (1.8–2.9)] and LBW [1.44 (1.1–1.9)]. Even in women without a recurrent PPROM, there was still a significant increase in PIH [1.4 (1.1–1.8)], PE [2.3 (1.6–3.5)], instrumental [2.2 (1.7–2.9)] and caesarean delivery [1.9 (1.5–2.4)], and neonatal unit admission [1.6 (1.3–2.0)]. Conclusions: PPROM in the first pregnancy is associated with significant adverse maternal and perinatal outcomes in the next pregnancy, but not reduced likelihood of second pregnancy. Tweetable abstract: PPROM in the first singleton pregnancy increases risk of adverse maternal and perinatal outcomes in the next singleton pregnancy. Tweetable abstract: PPROM in the first singleton pregnancy increases risk of adverse maternal and perinatal outcomes in the next singleton pregnancy. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14462 .